A novel CBCT staging method to determine spheno-occipital synchondrosis ossification. - Prof Muralidhar Mupparapu; Mr Anwar Radwan; Mr Muhammad Shammaa; Mr. Khartik Uppalapati; Miss Maanya Chitrapu (Elsevier, 2023)
Aim or Purpose: Our study seeks to classify the fusion of spheno-occipital synchondrosis (SOS) into 5 distinct novel stages based on CBCT visualization of SOS ossification. Materials and Methods: IRB-exempted protocol (#830154) was used to analyze CBCTs of 69 male and 67 female patients between the ages 5 and 25 using Osirix® and ITK SNAP® software. Midsagittal sections were sliced at 1mm to visualize the SOS. The mid-sagittal images were then organized based on gender and labeled according to the patient chronological age in years and months. These images were then classified using our novel 5-stage method. The 5 respective stages we developed are- SOS open (stage 1), the commencement of ossification (stage 2), less than 50% ossification at SOS (stage 3), greater than 50% ossification at SOS (stage 4), complete ossification of SOS (stage 5). Results: In our investigation thus far, it was noted that SOS ossification begins around 9.3 years in males and 8.7 years in females and is usually completely fused by the age of 17.8 for males and 14.9 for females. Conclusions: SOS is a cartilaginous cranial growth center that fuses the occipital and sphenoid bones during adolescence and can be used to assess the skeletal age of an orthodontic patient more accurately than existing methods without subjecting the patient to any additional radiation. Using the staging system proposed here, one can reliably and accurately determine the skeletal age of a patient. Our skeletal age estimation method may be used independently or as a supplement to hand-wrist radiographs and Cervical Vertebral Maturation.